Membrane feeding Glossina morsitans centralis on livestock blood and its effect on the tsetse susceptibility to pathogenic trypanosome infections - Moloo, S.K.; Karia, F.W.; Okumu, I.O. (1999)
Colonies of tsetse flies at ILRI were previously maintained in vivo on rabbits, and surplus teneral tsetse were used for various experiments. The reason for maintaining colony tsetse on live hosts was that all experimental tsetse, both trypanosome infected as well as uninfected were fed on experimental livestock, and it was therefore logical to maintain them as naturally as possible. However, in order to reduce the cost of maintaining colony tsetse and avoid discomfort to the rabbits, it was decided to switch to the artificial feeding system (Bauer & Wetzel, 1976; news et al 1977). Thus, studies were carried out to determine the type of blood that would provide optimum nutrition to the tsetse and to find the effect of maintaining infected tsetse through membranes upon fresh defibrinated bovine blood on their trypanosome infection prevalences. Glossina morsitans centralis Machado, stocks of T. vivax Ziemann, T. Congolense, and T. brucei, brucei clones were used. The animals used as blood donor were yearling Boran steers, and Gamma-irradiated sterile defibrinated bovine and porcine blood used were imported from the International Atomic Energy Agency (IAEA).